Family Planning Knowledge, Attitudes, and Practices among Married Men and Women in Rural Areas of Pakistan: Findings from a Qualitative Need Assessment Study - Mustafa, Ghulam; Azmat, Syed Khurram; Hameed, Waqas; Ali, Safdar; Ishaque, Muhammad; Hussain, Wajahat; Ahmed, Aftab; Munroe, Erik (International Journal of Reproductive Medicine, 2015)
This paper presents the findings of a qualitative assessment aimed at exploring knowledge, attitudes, and practices regarding family planning and factors that influence the need for and use of modern contraceptives. A descriptive exploratory study was conducted with married women and men aged between 15 and 40. Overall, 24 focus group discussions were conducted with male and female participants in three provinces of Pakistan. The findings reveal that the majority knew about some modern contraceptive methods, but the overall contraceptive use was very low. Knowledge and use of any contraceptive method were particularly low. Reasons for not using family planning and modern contraception included incomplete family size, negative perceptions, in-laws’ disapproval, religious concerns, side-effects, and lack of access to quality services. The majority preferred private facilities over the government health facilities as the later were cited as derided. The study concluded the need for qualified female healthcare providers, especially for long term family planning services at health facilities instead of camps arranged occasionally. Addressing issues around access, affordability, availability, and sociocultural barriers about modern contraception as well as involving men will help to meet the needs and ensure that the women and couples fulfill their childbearing and reproductive health goals.